ANALYSIS OF ARTERIAL AND VENOUS BLOOD GASES: THE ROLE OF MEDICAL CHEMISTRY IN MAINTAINING ACID–BASE BALANCE - Shukrullayeva Dilnoza; Baxtiyorova Jasmina (Modern American Journals, 2025)
Arterial and venous blood gas analysis is a critical tool in veterinary medicine for evaluating a patient's ventilation, oxygenation, and acid–base status. This paper explores the principles and clinical applications of blood gas interpretation in animals, with a focus on the six-step method of arterial blood gas (ABG) analysis. Key physiological parameters such as pH, PaCO₂, HCO₃⁻, and PaO₂ are discussed in detail, along with expected compensatory responses in various acid–base disorders. The paper also highlights the importance of proper sample collection, storage, and the role of point-of-care testing (POCT) devices in veterinary settings. Special consideration is given to how clinical context, environmental factors, and patient temperature affect interpretation. Based on the work of Harold Davis and other key sources, this review aims to provide veterinary students and practitioners with a comprehensive understanding of blood gas evaluation, enabling accurate diagnosis and improved clinical outcomes.
Keywords: Arterial blood gas (ABG), venous blood gas, acid–base balance, pH, PaCO₂, HCO₃⁻, PaO₂, oxygenation, ventilation, metabolic compensation, respiratory compensation, veterinary critical care, point-of-care testing (POCT), Harold Davis, blood gas interpretation, sample collection.